2023
DOI: 10.1063/5.0148236
|View full text |Cite
|
Sign up to set email alerts
|

CrB-type, ordered α-MnB: Single crystal structure and spin-canted magnetic behavior

Abstract: Manganese monoboride has a low- (α) and a high-temperature (β) modification, as well as a defect-rich low-temperature variant (α′). The crystal structure (FeB-type structure, s.g. Pnma) and properties of high-temperature MnB are well-known. In this work, single crystals were grown via chemical vapor transport reactions, both of β-MnB and the low-temperature modification, α-MnB. This allowed for determining the crystal structure of defect-free α-MnB [CrB-type structure, s.g. Cmcm, a = 3.0098(6) Å, b = 7.6390(2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Research on the properties and applications of magnetic materials is another important theme of this Special Issue. Examples include studies on the single crystal structure and spin-canted magnetic behavior of α-MnB reported by Kalyon et al, 14 the complex magnetic ordering behavior of the double perovskite Ba 2 MnMoO 6 using a combination of local and crystallographic probes by Coomer et al, 33 and the magnetocaloric effect of the lanthanide fluorides (Dixey et al 34 ). In addition, Nandwana and Dravid 35 demonstrate that the magnetic properties of the ferrite-spinel-based magnetic nanostructures can be enhanced by tuning their crystal chemistry and these nanostructures can act as a contrast agent in magnetic resonance imaging.…”
Section: Editorial Pubsaiporg/aip/apmmentioning
confidence: 99%
See 1 more Smart Citation
“…Research on the properties and applications of magnetic materials is another important theme of this Special Issue. Examples include studies on the single crystal structure and spin-canted magnetic behavior of α-MnB reported by Kalyon et al, 14 the complex magnetic ordering behavior of the double perovskite Ba 2 MnMoO 6 using a combination of local and crystallographic probes by Coomer et al, 33 and the magnetocaloric effect of the lanthanide fluorides (Dixey et al 34 ). In addition, Nandwana and Dravid 35 demonstrate that the magnetic properties of the ferrite-spinel-based magnetic nanostructures can be enhanced by tuning their crystal chemistry and these nanostructures can act as a contrast agent in magnetic resonance imaging.…”
Section: Editorial Pubsaiporg/aip/apmmentioning
confidence: 99%
“…This Special Collection embraces materials chemistry in its entire breadth and depth-in terms of materials classes, characterization techniques, and the close entanglement of experiment and theory. In keeping with the unique scope of materials chemistry pioneered by Professor Cheetham, the materials classes reported in this Special Issue span from MOFs to zeolites and metal oxides, borides (Hu et al 13 and Kalyon et al 14 ), and fluorides, and from DNA mesogens (Gallagher et al 15 ) to polyaniline (Sonu et al 16 ) and molecular organic crystals (Mu et al 17 ).…”
mentioning
confidence: 99%